Looking for indicator bird species in the context of forest fragmentation and isolation in West Kalimantan, Indonesia - Simamora, T.I.; Purbowo, S.D.; Laumonier, Y. (Elsevier, 2021)
In the context of Borneo’s drastic landscape fragmentation, we assessed the role of diverse forest and land uses—swidden agriculture, mixed garden, smallholder rubber and oil palm plantations—in determining (1) diversity levels and composition of bird species in different vegetation types; (2) the potential for bird species to act as indicators of habitat quality; and (3) the agricultural matrix’s contribution to preserving forest-dependent species. Field campaigns across West Kalimantan sites were conducted during both rainy and dry seasons, using mist nets and 10-min point count recordings along transects. We used four diversity indices, non-metric multidimensional scaling (NMDS) and the Indicator Value index (IndVal) for our analysis. Our results endorsed the general trend found across the tropics of a significant reduction in bird species richness, from the complex natural and old secondary forest structures to the simplified monoculture habitats. We recorded 10,519 individuals across 214 bird species, representing almost 90% of Borneo’s lowland forest species. NMDS differentiated intact forest from forest fragments and land under different agriculture uses. Eighty percent of the bird species preferred an intact forest environment. Industrial oil palm sites were the most ‘avoided’ vegetation type. Using IndVal, we found six indicator species significantly associated with forest, three indicator species for depleted forest, one for mixed garden, and none for oil palm plantation. Farm-dependent species richness was strikingly low, and species had little conservation value as per IUCN standards; industrial oil palm plantations were poorest in bird species. Notable exceptions were traditional mixed gardens and old fallows associated with swidden agriculture, when in proximity to forest. These traditional agroforestry systems have higher conservation value than industrial and smallholder monoculture plantations, however, their long-term preservation is uncertain, and monitoring programs are lacking that can contribute to long-term biodiversity conservation and ecosystem service maintenance. More data are needed to determine the viable population sizes for the bird indicator species identified in our study. Such knowledge on population trends can be used to monitor habitat quality and health of forest agriculture landscape mosaics and improve the effectiveness of management, conservation and monitoring in future.